Il pensiero della poesia Da Leopardi ai contemporanei. Letture dal mondo di poeti italiani - Minardi, Enrico; Caracchini, Cristina (Studi e saggi, 2017)
What is the common aspect linking the studies of this volume, which take into account very different authors such as Conte, Palazzeschi, Zanzotto, Caproni, Rosselli, Biagini, some crespuscolar poets, Leopardi, Annovi, Giuliani, and even some twentieth-century translations of R.M. Rilke? They share the belief that the poetic word - which etymologically has "creative" powers - generates cognitive perspectives altering our perception of the world. Reading poetry does not have an effect confined to the page and to the moment, but affects our relationship with reality, changes it and enriches it in an often unsuspected and surprising way. In this collection, the authors try to bring out a sort of epistemology of poetry, in order to clarify how it can contribute to illuminating our experience of the world and of ourselves. The reader is then invited to look beyond the boundaries traditionally established by the various disciplines, in the direction of mutual contamination and openness to innovative and unprecedented suggestions.